Ca2+ images obtained in different experimental conditions shed light on the spatial distribution of IP3 receptors that underlie Ca2+ puffs - Piegari, Estefanía (2015)
Many intracellular Ca2+ signals involve Ca2+ release from the endoplasmic reticulum through inositol 1,4,5-trisphosphate receptors (IP3Rs). The open probability of IP3Rs depends on cytosolic Ca2+ so that these signals involve Ca2+-induced Ca2+-release (CICR). IP3Rs are organized in clusters. The signals they mediate are observed using single-wavelength dyes and, often, a slow Ca2+ buffer (EGTA) is added to disrupt CICR between clusters and keep the signals spatially restricted. It is assumed that the presence of the dye or of EGTA does not alter the intra-cluster Ca2+ dynamics. In this paper we analyze this issue combining experiments and numerical simulations. We compare the properties of local signals known as puffs observed with different dyes and EGTA concentrations. We determine that although the dye or EGTA does not alter the intra-cluster dynamics, the set of observable events is different depending on the degree of inter-cluster uncoupling of the experiment. An analysis of the observations shows that the events that are missed for insufficient inter-cluster uncoupling are those of fastest amplitude growth rate. This agrees with a spatial organization in which the largest amplitude events correspond to clusters with densely packed active IP3Rs.